Home Respiratory Polygraphy to Detect Obstructive Sleep Apnea Syndrome after Supracricoid Partial Laryngectomy - Hernández-Sandemetrio, Rosa; Oishi, Natsuki; Chavero, Tomás; Navarro, Rafael; López, Isabel; Zapater, Enrique (International Archives of Otorhinolaryngology, 2025)
Introduction Supracricoid partial laryngectomy is a surgical treatment for advanced laryngeal cancer which is implemented to preserve organ function, but it may cause obstructive sleep apnea syndrome (OSAS) due to anatomical changes after surgery that may be neglected by clinicians.Although the gold standard for the diagnosis of OSAS is polysomnography, respiratory polygraphy is an alternative valid method with a high level of diagnostic sensitivity and specificity; since the equipment is portable, it can be used at home, with no need for hospitalization.Objective To describe the polygraphy result of patients submitted to supracricoid partial laryngectomy.Methods The present study included 13 patients, and we collected data on age, date of the surgery, body mass index, cardiovascular risk factors, Epworth score, and apnea-hypopnea index (AHI).Results The 13 patients were all male, with a mean age of 62 years. As for the AHI, one patient was classified as severe, six, as moderate, and three patients, as mild; moreover, 3 patients were simple snorers. While 77% of the sample presented OSAS, only 23% presented symptoms of drowsiness.Conclusion The study group, who underwent supracricoid partial laryngectomy, did not present self-reported symptoms of OSAS. Nevertheless, polygraphy was a useful tool in this group, and we recommend its systematic use after decannulation to avoid leaving OSAS undiagnosed.Level of evidence 4; case series study
Keywords: obstructive sleep apnea; partial laryngectomy; polygraphy